Emerging growth factor receptor antagonists for ovarian cancer treatment. (2nd January 2018) - Bonilla, Luisa; Oza, Amit; Lheureux, Stephanie
ABSTRACT: Introduction : Epithelial Ovarian Cancer (EOC) is the most lethal gynecological malignancy. EOC outcomes remain unsatisfactory despite aggressive surgical approach, disease chemo-sensitivity and recent introduction of agents targeting angiogenesis and tumour genome instability. Advances in EOC research have allowed for a tailored treatment approach and accelerated development of novel treatments strategies from bench to bed side, anticipated to improve patient outcomes. Areas covered : Comprehensive review of growth factor receptor antagonists for EOC treatment currently in different stages of development was performed. English peer-reviewed articles and abstracts were searched in MEDLINE, PubMed, Embase and major conferences. We focused on agents that antagonize growth factors promoting sustained proliferative signaling, angiogenesis and evasion of immune destruction blocking the receptor or its stimulating factors. Expert opinion : Receptor signaling has been well characterized for most cancer generating pathways. Growth receptor antagonists are represented by both high receptor affinity monoclonal antibodies as well as tyrosine kinase inhibitors; both are especially effective when a related predictive biomarker of response is identified. Therefore, along with the promising development of novel receptor antagonists or modulators in EOC treatment, targeting essential growth pathways in the tumour and associated microenvironment, is fundamental for biomarker discovery and towards achieving significant improvements in response.